Controlled Covalent Functionalization of 2 H-MoS2 with Molecular or Polymeric Adlayers - Quirós-Ovies, Ramiro; Vázquez Sulleiro, Manuel; Vera-Hidalgo, Mariano; Prieto, Javier; Gómez, I Jénnifer; Sebastián, Víctor; Santamaría, Jesús; Pérez, Emilio M (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
Most air-stable 2D materials are relatively inert, which makes their chemical modification difficult. In particular, in the case of MoS2 , the semiconducting 2 H-MoS2 is much less reactive than its metallic counterpart, 1T-MoS2 . As a consequence, there are hardly any reliable methods for the covalent modification of 2 H-MoS2 . An ideal method for the chemical functionalization of such materials should be both mild, not requiring the introduction of a large number of defects, and versatile, allowing for the decoration with as many different functional groups as possible. Herein, a comprehensive study on the covalent functionalization of 2 H-MoS2 with maleimides is presented. The use of a base (Et3 N) leads to the in situ formation of a succinimide polymer layer, covalently connected to MoS2 . In contrast, in the absence of base, functionalization stops at the molecular level. Moreover, the functionalization protocol is mild (occurs at room temperature), fast (nearly complete in 1 h), and very flexible (11 different solvents and 10 different maleimides tested). In practical terms, the procedures described here allow for the chemist to manipulate 2 H-MoS2 in a very flexible way, decorating it with polymers or molecules, and with a wide range of functional groups for subsequent modification. Conceptually, the spurious formation of an organic polymer might be general to other methods of functionalization of 2D materials, where a large excess of molecular reagents is typically used.
Keywords: maleimide; MoS2; covalent functionalization; click chemistry; 2D materials